Antimicrobial and anti oxidant activities of an Endophytic fungi Isolated from an endemic medicinal plant Pterocarpus santalinus - Nagam venkateswarlu; Tartte Vijaya; Netala Vasudeva Reddy; K. K. Shama (International Journal of Phytomedicine, 2014)
Endophytic fungi are intriguing microorganisms live inside the healthy plant tissues. they are quite diverse in nature and have enormous potential for production of important secondary metabolites of biomedical, pharmaceutical and clinical importance. In the present work we have isolated an endophytic fungi from the leaves of Pterocarpus santalinus an endemic medicinal plant of Eastern ghats, Tirumala hills, India. Based on the molecular characterization by 18S rRNA analysis the fungi was identified as Xylaria spp. ENT2 (Accession No. KF493856.1). the crude extract of Xylaria sp. was evaluated for antioxidant and antimicrobial activities. Among the other extracts tested methanolic extract showed highest activity against all the bacterial and fungal pathogens with a minimum bactericidal concentration (MBC) of about 30μg/mL against Staphylococcus aureus and a Minimum Fungicidal Concentration (MFC) of about 50μg/mL against Candida albicans. Similarly methanolic extract proved to be potential natural antioxidant with 56.26±0.08 radical scavenging activity (RSA).